Efficiency of bioinsecticides in the control of Mahanarva fimbriolata (Hemiptera: Cercopidae) in field conditions (Research, Society and Development, 2020)
When feeding on the roots, the nymphs of Mahanarva fimbriolata they cause lesions in the vascular system, compromising the transport of water and nutrients to the meristematic regions of the plant. The aim of this study was to evaluate the control efficiency of M. fimbriolata using commercial isolates of M. anisopliae and imidacloprid insecticide in field conditions. The experimental design was in randomized blocks with 4 treatments: Metarril®, Metiê®, Evidence® 700 WG, Control; and 4 repetitions with 750 m2 each. Bioinsecticides were applied at a concentration of 1.5×1012 viable conidia per hectare and the insecticide Evidence® 700 WG at a dose of 400 g ha-1 of the commercial product. Evaluations were performed at 30, 60, 90 and 120 days after application and the data were submitted to the F test, Tukey's test at P ≤ 0.05 and efficiency calculated using the Abbott formula. All bioinsecticides provided a high reduction in the number of leafhopper nymphs (95%) from 30 to 120 days after spraying (DAP). At 60, 90 and 120 DAP the bioinsecticides provided above 84% efficiency when compared to the insecticide. For adults, the bioinsecticides Metarril® and Metiê® caused a greater reduction in live insects and were more efficient than the insecticide Evidence® 700 WG, providing 100% efficiency. The bioinsecticides Metarril® and Metiê® provided better performance, being efficient in the management of M. fimbriolata.